Islam and entrepreneurship: The compatibility study from the Qur'an and Sunnah - Sani, Muhammad Baffa (2017)
This study examines the compatibility of Islam and entrepreneurship from the Qur’an and Sunnah by assessing the Islamic view on innovativeness, proactiveness and risks taking that are often considered the key components that measure forms of entrepreneurial orientations. It is discovered that all the variables are enjoined by Islam thus, it is concluded that Islam and Entrepreneurship are highly compatible.Therefore, the study recommends Muslims to fully engage in the search and acquisition of knowledge because, all the variables are knowledge-bound and equally, knowledge acquisition is the fundamental teaching of Islam.